1975
DOI: 10.1002/pol.1975.170130219
|View full text |Cite
|
Sign up to set email alerts
|

Donor–acceptor complexes in copolymerization. XLIX. Cationic polymerization of donor monomers in presence of polar solvents and acrylic monomers. A revised mechanism for polymerization of comonomer complexes

Abstract: Abstractα‐Methylstyrene (MS) and isobutyl vinyl ether (VE) readily polymerize, styrene (S) polymerizes to a small extent, and isobutylene (IB), butadiene (BD), and isoprene (IP) fail to polymerize in the presence of catalytic amounts of AlCl3 when propionitrile, ethyl propionate, and methyl isobutyrate are used as reaction media. MS polymerizes readily and S polymerizes with difficulty in the presence of AlCl3 to yield homopolymers when acrylonitrile (AN) is present and copolymers with ethyl acrylate (EA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
2

Year Published

1979
1979
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 13 publications
0
2
2
Order By: Relevance
“…51 Therefore, it was erroneously assumed that the mechanism of such copolymerization was not radical in nature. 52 Our results disagree with this assumption; however, the polydispersity index was found to be higher in the presence of Et 2 AlCl than in its absence. This behavior is possibly a consequence of the complexation of cumyl dithiobenzoate end groups with the Lewis acid.…”
Section: Study Of Raft Copolymerization Of Styrene and Methyl Methacr...contrasting
confidence: 99%
See 1 more Smart Citation
“…51 Therefore, it was erroneously assumed that the mechanism of such copolymerization was not radical in nature. 52 Our results disagree with this assumption; however, the polydispersity index was found to be higher in the presence of Et 2 AlCl than in its absence. This behavior is possibly a consequence of the complexation of cumyl dithiobenzoate end groups with the Lewis acid.…”
Section: Study Of Raft Copolymerization Of Styrene and Methyl Methacr...contrasting
confidence: 99%
“…During the 1970s, it was shown that alternating copolymerizations conducted in the presence of Lewis acids were relatively insensitive to the presence of transfer agents such as carbon tetrachloride . Therefore, it was erroneously assumed that the mechanism of such copolymerization was not radical in nature . Our results disagree with this assumption; however, the polydispersity index was found to be higher in the presence of Et 2 AlCl than in its absence.…”
Section: Resultscontrasting
confidence: 74%
“…Methacrylic monomers can, in fact, be used as solvents or colsolvents in the formation of polymer by a cationic mechanism (95,96).…”
Section: Ionic Polymerization Cationic Polymerization Is Not An Optimentioning
confidence: 99%
“…The domains of variation or the concentration ranges of the variables were selected from the experimental results of various workers [19,23,24].…”
Section: Design Of the Experimentsmentioning
confidence: 99%